How Could the Pacific Restore International Travel? - Blackman, Andrew (World Bank, Sydney, 2021)
With some COVID-19 vaccines now approved and starting to be rolled-out in several countries globally, Papua New Guinea (PNG) and the Pacific Island Countries (PICs) are considering how they can restore international travel with the rest of the world. This report outlines three potential sequential phases of border entry policy in PNG and the PICs: 1. Establishing international travel for cohorts of specific types of travelers; 2. COVID-19 safe travel corridors; 3. A ‘new normal’ – which could involve some combination of: (i) widely available vaccine(s) or treatment; (ii) accurate, rapiddiagnostic and antibody testing; and (iii) fit-for-purpose tracing and health-surveillance capacity.